FORMULASI EKSTRAK ETANOL DAUN SALAM (Eugenia polyanthum Weight) DALAM SEDIAAN GRANUL EFFERVESCENT - A. Muflihunna (As-Syifaa Jurnal Farmasi, 2009)
A research of effervescent granule has been done of ethanol extract of eugenia leaf in variation of acid and carbonate sources as well as lactose as the adsorbent. The ratio between extract and lactose were 1 : 0,5, 1 : 1 and 1 : 2 resepectively in formula A, B, C. This aim was determine the best pharmaceutic properties of granule. The evaluation carried out by organoleptic, lost of drying, angle of repose, flowbility, porosity, and dispersibility analyse by block random design showed that formula (has the lowest lost of drying than formula B and A). Formula C has the highest flowbility. Mean while in dispersibility exhibited formula C was the slowest one. Conclusion that might be draw that formula C in ratio 1 : 2 has  the best pharmaceutics properties.Key words : Eugenia polyanthum Weight, effervescent, formulation